Cholesteatoma: An Updated Review of Molecular Pathogenesis and Potential Therapeutic Directions - Xing, Bingwen; Dang, Yalong; Xi, Kai (Current Medicinal Chemistry, 2026)
Cholesteatoma, an abnormal accumulation of keratinized squamous epithelium in the middle ear, occurs as a locally invasive but histologically benign lesion. Its capacity for bone erosion leads to significant complications, including hearing loss, facial nerve paralysis, and intracranial infections. Chronic inflammation is central to its pathogenesis, with proinflammatory mediators like TNF-α, IL-1β, and IL-6 activating signaling pathways, such as NF-κB, JAK/STAT, and MAPK. These pathways contribute to epithelial hyperproliferation and extracellular matrix degradation mediated by Matrix Metalloproteinases (MMPs). Dysregulation of epithelial cell behavior, involving altered keratinocyte function and reduced E-cadherin-mediated adhesion, may facilitate lesion formation and expansion. Furthermore, aberrant signaling involving growth factors (e.g., EGF, TGF-β) and dysregulation of osteoclast activity via the RANKL pathway contribute to enhanced bone erosion and tissue invasion. Emerging research highlights potential roles of the c-MYC proto-oncogene, microRNAs, and Sonic hedgehog signaling in disease progression, offering deeper insights into the pathogenesis. Current management primarily involves surgical excision, yet high recurrence rates emphasize the need for adjunctive therapeutic strategies. Potential future directions include modulating key pathways, such as NF-κB, MMP activity, and RANKL signaling, as well as exploring interventions related to growth factors and cell adhesion. Integrating molecular insights with clinical research is essential for developing strategies to reduce recurrence and improve patient outcomes.
Keywords: bone resorption